The Important Role of Halogen Bond in Substrate Selectivity of Enzymatic Catalysis - Jiang, Shuiqin; Zhang, Lujia; Cui, Dongbin; Yao, Zhiqiang; Gao, Bei; Lin, Jinping; Wei, Dongzhi (Scientific reports, 2016)
The use of halogen bond is widespread in drug discovery, design, and clinical trials, but is overlooked in drug biosynthesis. Here, the role of halogen bond in the nitrilase-catalyzed synthesis of ortho-, meta-, and para-chlorophenylacetic acid was investigated. Different distributions of halogen bond induced changes of substrate binding conformation and affected substrate selectivity. By engineering the halogen interaction, the substrate selectivity of the enzyme changed, with the implication that halogen bond plays an important role in biosynthesis and should be used as an efficient and reliable tool in enzymatic drug synthesis.